Objective assessment of progressive increase in bite force post surgical correction of mandibular fractures using Nupai bite scan analyser - Rafique, Soheb; Rakesh, Devika; Uppal, Sanjeev K.; Garg, Ramneesh; Mittal, Rajinder K.; Shah, Sheerin (International Journal of Research in Medical Sciences, 2021)
Background: Fracture of mandible is a common condition which is increasing in incidence in the trauma centers due to increasing motor vehicles and failure to abide by traffic regulations. Patients undergo surgical open reduction and internal fixation where post-operative occlusion and normal masticatory functions are targeted. Bite force can be taken as a guide of normal masticatory function of an individual which is dependent upon craniomandibular biomechanics. The aim of the study was to analyse bite force measurements post-operatively in patients who underwent open reduction and internal fixation for mandible fractures at different sites. Methods: Molar bite force was recorded in 31 post-operative patients who underwent open surgical procedure for fracture mandible in the department of plastic surgery from January 2018 to June 2019 by a pre-scale bite force recorder-Nupai bite force prescale system (FujiTM). Various parameters were recorded pre and post-operatively including age, gender, history, comorbidities, requirement of MMF, site and number of fractures and age of injury. Bite force were compared and improvement of bite force every 2 weeks was noted and analyzed upto 6 weeks postoperatively. Results: Bite force improvement was seen in all types of mandible fractures irrespective of the site and type of fractures over a period of 6 weeks post-operatively. This improvement was however not statistically significant. Decreased time interval form injury to surgery resulted in improved bite force measurements though not statistically significant. Conclusions: Although objective improvement in bite force could be demonstrated but extensive study involving more subjects and more patient variables would have statistical significance.